Modeling of a Segmented Electrode for Desynchronizing Deep Brain Stimulation - Buhlmann, Julia; Hofmann, Lorenz; Tass, Peter A.; Hauptmann, Christian (Frontiers in Neuroengineering, 2011)
Deep brain stimulation (DBS) is an effective therapy for medically refrac- tory movement disorders like Parkinson’s disease. The electrodes, implanted in the target area within the human brain, generate an electric field which activates nerve fibers and cell bodies in the proximate vicinity. Even though the different target nuclei display considerable differences in their anatomical structure, only few types of electrodes are currently commercially available. It is desirable to adjust the electric field and in particular the volume of tissue activated around the electrode with respect to the corresponding target nucleus in a such way that side effects can be reduced. Furthermore, a more selective and partial activation of the target structure is desirable for an optimal application of novel stimulation strate- gies, e.g. coordinated reset neuromodulation. Hence we designed a DBS electrode with a segmented design allowing a more selective activation of the target struc- ture. We created a finite element model (FEM) of the electrode and analyzed the volume of tissue activated for this electrode design. The segmented electrode ac- tivated an area in a targeted manner, of which the dimension and position relative to the electrode could be controlled by adjusting the stimulation parameters for each contact. According to our computational analysis, this directed stimulation might be superior with respect to the occurrence of side effects and it enables the application of coordinated reset neuromodulation under optimal conditions.